Spatial activity-based modeling for pedestrian crowd simulation. (April 2013) - Qiu, Fasheng; Hu, Xiaolin
This paper proposes a spatial activity-based modeling approach and applies it to pedestrian crowd behavior simulations. Compared to conventional pedestrian crowd models where pedestrians make movement decisions in a time-based manner, the spatial activity-based pedestrian crowd model allows a pedestrian to make decisions only when needed, that is, when there is significant change in the pedestrian's spatial position, as defined by a threshold called 'space resolution'. To demonstrate the spatial activity-based modeling, we develop an activity-based model for pedestrian crowd simulation in a two-dimensional environment and compare it with a conventional time-based simulation model. Experiment results show that the spatial activity-based model can lead to more efficient simulations when simulating heterogeneous pedestrian crowds.